Composted biosolids and treated wastewater as sources of pharmaceuticals and personal care products for plant uptake: A case study with carbamazepine. (January 2018) - Ben Mordechay, Evyatar; Tarchitzky, Jorge; Chen, Yona; Shenker, Moshe; Chefetz, Benny
Abstract: Irrigation with treated wastewater (TWW) and application of biosolids to arable land expose the agro-environment to pharmaceuticals and personal care products (PPCPs) which can be taken up by crops. In this project, we studied the effect of a carrier medium (e.g., biosolids and TWW) on plant (tomato, wheat and lettuce) uptake, translocation and metabolism of carbamazepine as a model for non-ionic PPCPs. Plant uptake and bioconcentration factors were significantly lower in soils amended with biosolids compared to soils irrigated with TWW. In soils amended with biosolids and irrigated with TWW, the bioavailability of carbamazepine for plant uptake was moderately decreased as compared to plants grown in soils irrigated with TWW alone. While TWW acts as a continuous source of PPCPs, biosolids act both as a source and a sink for these compounds. Moreover, it appears that decomposition of the biosolids in the soil after amendment enhances their adsorptive properties, which in turn reduces the bioavailability of PPCPs in the soil environment. In-plant metabolism of carbamazepine was found to be independent of environmental factors, such as soil type, carrier medium, and absolute amount implemented to the soil, but was controlled by the total amount taken up by the plant. Graphical abstract: Highlights: Bioaccumulation of carbamazepine is higher in plants irrigated with TWW than in plants grown in soils applied with biosolids. Application of composted biosolids reduces the bioavailability of carbamazepine originated from TWW irrigation. Plant metabolism of carbamazepine is affected by the total amount taken-up by the plant. Abstract : Bioavailability of PPCPs originated from biosolids amendment is lower than the bioavailability of those introduced by irrigation with treated wastewater.